A comprehensive analysis of LMO2 pathogenic regulatory profile during T-lineage development and leukemic transformation - Wang, Wenhao; Meng, Yingying; Chen, Yaxin; Yu, Yanhong; Wang, Hang; Yang, Shuang; Sun, Wei (Oncogene, 2022)
LMO2 is a well-known leukemic proto-oncogene, its ectopic expression in T-lineage specifically initiates malignant transformation of immature T cells and ultimately causes the onset of acute T-lymphocytic leukemia (T-ALL) in both mouse models and human patients. In this study, we systematically explored the LMO2 performance on the profiles of transcriptome, DNA-binding and protein interactions during T-lineage development in the pre-leukemic stage. Our data indicated that large-scale transcriptional dysregulation caused by LMO2 primarily occurred in DN3 thymocytes, characterized by enriched upregulation of the target genes of typical LMO2 complex, RUNX, ETS and STATs, and ectopic LMO2 primarily targeted to RUNX motifs along with intensive interaction with RUNX1 and H3K4 methyltransferase component ASH2L in this stage. However, binding of LMO2 on specific motifs was largely reduced in the following DP and SP stages, along with gradually disappeared LMO2-RUNX1 and LMO2-ASH2L interactions and less alteration of certain transcriptional factor profiles. Moreover, LMO2 showed relatively less influence on cellular behavior of DN3 thymocyte whereas displayed more prominent effects in DP and SP stages, including promoting Notch signaling and cell cycles. These findings provide a high-resolution landscape of the pathogenic role of LMO2 during T-lineage development in molecular level, and may benefit further clinical investigations for LMO2-associated T-lineage malignancies.